COMPARISON OF CENTRAL CORNEAL THICKNESS IN PSEUDOEXFOLIATION GLAUCOMA PATIENTS WITH HEALTHY ADULTS: Central Corneal Thickness in Glaucoma Patients - Malik, Saad Mushtaq; Rauf, Ali; Saeed, Shahzad (Pakistan Armed Forces Medical Journal, 2016)
ABSTRACT Objective: To compare the central corneal thickness (CCT) in pseudoexfoliation glaucoma (PXG)patients with healthy adults. Study Design: Cross-sectional comparative study. Place and Duration of Study: Armed Forces Institute of Ophthalmology Rawalpindi, from Dec 2009 to Feb 2011. Material and Methods: 30 patients having PXG (Group A) and 30 healthy adults having normal intraocular pressure (Group B) were included in the study. Intraocular pressure (IOP) in both groups was measured using gauged Goldmann applanation tonometer (GAT).Central corneal thickness (CCT) was measured with an ultrasonic pachymeter. Results: The comparison of Mean CCT in both Groups showed that Mean CCT was significantly lesser ( p-value <0.05) in PXG Group (519.73 μm) as compared to healthy adults Group (567.48 μm). Conclusion: CCT in PXG patients group was found to be statistically significantly thinner as compared to healthy adults Group. CCT must be assessed in patients with pseudoexfoliation syndrome (PXF) in order to avoid the underestimation of IOP.